The Effects of Day/Night Forcing Temperature Regimes, Growth Retardants and Ethephon Treatments on Tulips (Tulipa Gesneriana Var 'Cassini') - Wong, Chee Ching (2004)
Three studies were conducted to determine the forcing procedures for potted tulip and postharvest treatments for cut tulips under tropical conditions. The objectives of the first study were to examine the protein profiles alteration associated with various daylnight forcing temperatures (26122, 26/18, 26/14, 22/18, 22/14 and 18/14 OC) and to identify a potential protein marker that is involved in producing a good quality tulip through the SDS-PAGE method. The experimental design used was an incomplete block design with three replications per treatment. There were no significant differences in plant height, perianth length, flower diameter, no. of days to first visible bud and no. of days to senescence for plants treated under different daylnight temperature regimes. Only scape length, no. of days to coloured bud stage and anthesis stage were significantly affected. Protein profiles ' 1 0 ? -y @ obtained fiom one dimensional gel electrophoresis from plants forced u$d& dikefen1 * daylnight temperatures showed no differences in protein banding patterns. Protein no. 2 at vegetative stage and protein no. 37 and 38 at anthesis stage were found to have potential as protein markers that could be involved in producing good quality tulip which was revealed in 2D gel electrophoresis. Second study was carried out in order to determine the optimal concentration of paclobutrazol and flurprimidol on height control of potted tulips. Two experiments were carried out by using two different growth redartants at different rates. In experiment I paclobutrazol at 0, 5, 10, 15, 20 and 25 mg.~-' were used while in experiment I1 flurprimidol was used at 0, 20, 40, 60, 80 and 100 mg.~-'. The experimental design used was a completely randomised design with five replications per treatment. In experiment I, plant height and scape length, perianth length and flower diameter were significantly affected by paclobutrazol treatment. There were no significant differences in no. of days to first visible bud, no. of days to coloured bud stage, no. of days to anthesis and no. of days to senescence. The optimal rate of paclobutrazol for height control of 'Cassini' tulip was 20 mg .~-w' ith reduction of 13.6% in plant height and 14.8% in scape length. In experiment 11, plant height, scape length, perianth and flower longevity were significantly affected by flurprimidol treatment. There were no significant differences in no. of days to first visible bud, no. of days to coloured bud stage, no. of days to anthesis and flower diameter. The optimal rate of flurprimidol in controlling plant height of 'Cassini' tulip was 40 mgL with reduction of 13.8% and 17.4% for plant height and scape length respectively. . .. .- Third study was carried out to determine the effect of ethephon pretreatment on stem elongation and flower longevity of cut tulips. Treatments comprised basal stem dip in ethephon at 0, 20, 40 and 60 mg.~-' for 0, 15 and 30 minutes. The experimental iii design used was a completely randomised design with five replications per treatment. Ethephon pretreatment significantly reduced the last internode length, scape length and flower opening rate. The reduction of stem length was due to the reduction in cell length which was revealed by histological study. Ethephon at 20 to 40 mg.~-' and duration of dipping time fiom 15 to 30 minutes were found to effective in overcoming the problem of stem elongation without reducing flower quality.